2011
DOI: 10.1123/ijspp.6.4.580
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Exercise Inter-Set Cooling Strategy: Effect on Performance and Muscle Damage

Abstract: Purpose:To compare the effect of inter-set cooling and no cooling during resistance exercise (RE) on the total repetitions and select muscle damage biomarker responses.Methods:Sixteen healthy men volunteered to participate in this study and were randomly assigned to Cooling (n = 8) or Control (n = 8) groups. They performed a RE protocol consisting of four sets of biceps curl at 80% of 1RM. The cooling group received the application of wet bags of ice during each inter-set rest interval (Cooling), while the Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…Decreased tissue temperature has been shown to reduce nerve conduction velocity, muscle force production and muscular power [60] [61] [62]. These observations are in line with the findings of Galoza et al (2011), demonstrating that external pre-cooling failed to significantly affect weight lifting activity in the biceps brachii muscle compared to a non-cooling strategy [40]. However, it has to be taken into account that only one study was included in the subgroup analysis of the present meta-analysis for as-…”
Section: External-cooling Vs Non-cooling Strategiessupporting
confidence: 78%
See 1 more Smart Citation
“…Decreased tissue temperature has been shown to reduce nerve conduction velocity, muscle force production and muscular power [60] [61] [62]. These observations are in line with the findings of Galoza et al (2011), demonstrating that external pre-cooling failed to significantly affect weight lifting activity in the biceps brachii muscle compared to a non-cooling strategy [40]. However, it has to be taken into account that only one study was included in the subgroup analysis of the present meta-analysis for as-…”
Section: External-cooling Vs Non-cooling Strategiessupporting
confidence: 78%
“…For the remaining three studies (10%), reporting bias remained unclear [39] [40] [41]. Additionally, it can be observed that the risk for selection bias (93% for sequence generation and 97% for allocation concealment) detection bias (100% for blinding of outcome assessment) and other bias (100%) remained unclear.…”
Section: Risk Of Bias Analysismentioning
confidence: 99%
“…Previous investigations have incorporated various intermittent cooling strategies during the rest periods of high-intensity resistance exercise to augment acute performance. These strategies have involved application of cooling directly on the agonist muscle undergoing exercise (8,10,30), distal to the agonist muscle undergoing exercise but on the same limb (1,3,8,11,17,18) (i.e., palm cooling for upper-body musculature), or distal to the agonist muscle undergoing exercise on a different limb (i.e., palm cooling during lower-body exercise) (4). Taken together, these studies have reported either a positive effect of cooling on acute resistance exercise performance compared with a control condition (3,4,10,17,18,30) or no effect on performance compared with a control condition (1,8).…”
Section: Discussionmentioning
confidence: 99%
“…These strategies have involved application of cooling directly on the agonist muscle undergoing exercise (8,10,30), distal to the agonist muscle undergoing exercise but on the same limb (1,3,8,11,17,18) (i.e., palm cooling for upper-body musculature), or distal to the agonist muscle undergoing exercise on a different limb (i.e., palm cooling during lower-body exercise) (4). Taken together, these studies have reported either a positive effect of cooling on acute resistance exercise performance compared with a control condition (3,4,10,17,18,30) or no effect on performance compared with a control condition (1,8). Aside from the chosen method of cooling application, these studies also investigated different agonists (such as pectorals, latissimus dorsi, biceps brachii, and quadriceps femoris), used different loading intensities (70-90% 1RM), different interset recovery periods (1-3 minutes), and different populations with varying degrees of resistance training experience (6 months to .5 years).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, understanding the acute physiological responses to isometric forearm muscle contractions in the cold is clinically relevant. Studies of adults exercising in cold environments are few and generally limited to those using varied methodology exploring either the control of cutaneous blood flow during exercise (46) or the performancerelated effects of cold acclimation (17,57,61). At thermoneutral temperatures, older adults exhibit either similar (21,40,49) or blunted (26,33,48) increases in MSNA and BP during static HG compared with the increases demonstrated in young adults.…”
Section: Discussionmentioning
confidence: 99%